Designing, implementing and sustaining IPE within an authentic clinical environment: the impact on student learning. Issue 6 (2nd November 2021) - Naumann, Fiona; Mullins, Robert; Cawte, Andrea; Beavis, Simon; Musial, Jane; Hannan-Jones, Mary
ABSTRACT: Interprofessional education (IPE), as preparation for interprofessional practice (IPP), is essential for quality, coordinated, outcome-focussed patient care. To develop capacity for IPP in future healthcare practitioners, IPE needs to be developed within curriculum and applied within authentic settings. The study aims were threefold: (a) determine if an established type 2 Diabetes Mellitus (T2DM) exercise and healthy lifestyle program could be replicated and delivered at a satellite health precinct; (b) report on changes in students' attitudes to IPP in response to involvement in the program; (c) explore the perceptions of students in response to participation in the program whilst on placement. This paper reports on the quantitative changes in perceptions of IPE as measured by the SPICE-R2 instrument and a qualitative analysis of the student reflection of participating in IPP. Thirty-five students, from 4 health professions, participated in the study. The quantitative outcomes showed significant improvement in the perceptions of IPE ( p <.01), including significant improvements understanding of roles and responsibilities, teamwork, and patient outcomes ( p <.01). The qualitative analysis included a subset of 18 students who participated across two focus groups, highlighting four key themes: (a) health students reported varied initial experience with, and understanding of IPE; (b) the IPE program enabled students to see the value of teamwork for patient care; (c) IPE enhanced role clarity amongst the students, and (d) the IPE program provided an authentic learning experience, best suited to final year students. Our findings reinforced the value of a partnership between higher education and health services to deliver IPP care and learning, student valuing of the importance of IPE as part of authentic learning, and need for a scaffolded approach toward IPE is needed across health curriculums, and clinical placement to ensure all students can develop IPE capabilities that will enable them to work together to deliver the best healthcare to clients.